Chemical and kinetic insights into the Thermal Decomposition of an Oxide Layer on Si(111) from Millisecond Photoelectron Spectroscopy - Gallet, J.-J. (Sci Rep, 2017)
Despite thermal silicon oxide desorption is a basic operation in semiconductor nanotechnology, its detailed chemical analysis has not been yet realized via time-resolved photoemission. Using an advanced acquisition system and synchrotron radiation, heating schedules with velocities as high as 100 K.s(−1) were implemented and highly resolved Si 2p spectra in the tens of millisecond range were obtained. Starting from a Si(111)-7 × 7 surface oxidized in O(2) at room temperature (1.4 monolayer of oxygen), changes in the Si 2p spectral shape enabled a detailed chemical analysis of the oxygen redistribution at the surface and of the nucleation, growth and reconstruction of the clean silicon areas. As desorption is an inhomogeneous surface process, the Avrami formalism was adapted to oxide desorption via an original mathematical analysis. The extracted kinetic parameters (the Avrami exponent equal to ~2, the activation energy of ~4.1 eV and a characteristic frequency) were found remarkably stable within a wide (~110 K) desorption temperature window, showing that the Avrami analysis is robust. Both the chemical and kinetic information collected from this experiment can find useful applications when desorption of the oxide layer is a fundamental step in nanofabrication processes on silicon surfaces.